Research of characteristics of working cycle of high-speed diesel engine operating on biofuels RME–E and D–RME–E. Part 2. Indicators and characteristics of heat release in diesel cylinder - Lebedevas, Sergejus; Lebedeva, Galina; Žaglinskis, Justas; Rapalis, Paulius; Gudaitytė, Ingrida (Transport, 2013)
This paper presents material about using two-component RME–E and three-component D–RME–E biodiesels in high-speed diesel engines. The results of the analysis of fuel injection parameters described in Part I of this scientific paper – Research of characteristics of working cycle of high-speed diesel engine operating on biofuels RME–E and D–RME–E. Part 1. Indicators of fuel injection system and indicative process – allow conducting a coherent research of heat release in the cylinder of diesel engines transferred from operation on mineral diesel D to mixed biodiesels containing E. Effects of increased ethanol E in the biodiesel of 1A41 diesel engine have been analysed in a wide range of loads, ranging from 0.25 to 1.0 Penom. It was found that the result of the transfer from two-phase heat release to one-phase heat release is an increase in the fuel’s economy of the engine for every 10% increase of E in the fuel (increase of indicative process efficiency makes up 0.4÷0.5%). Dependency of heat release and nitrogen oxide emissions in the exhaust gases remains the same for mineral diesel, RME–E and D–RME–E. Indicators of cyclic stability of the diesel engine, operating on biodiesels containing E ≤ 30%, did not exceed those that are common for diesel engines operating on mineral diesel. First Published Online: 11 Oct 2013